KINERJA PEGAWAI DINAS PARIWISATA PROVINSI SULAWESI TENGAH - Arif, Mohammad (Katalogis, 2018)
By looking at the existing problems at the Department of Tourism Sulawesi province seemed a decrease in employee performance so that research conducted in order to determine the performance of employees Department of Tourism Central Sulawesi province. Using descriptive qualitative research methods. The number of informants in this study that eight people, drawn by pusposive sampling techniques. Mechanical collection and retrieval of data consists of observations, interviews, and documentation. The theory used in view of employee performance that is the theory put forward by Dessler, the concept as a measure of performance for Employees at the Department of Tourism Central Sulawesi province. The results showed that the performance of employees at the Department of Tourism of Central Sulawesi province can be seen from the aspect. First, the quality of work of employees showed a pretty good performance. Second, the quantity of employee jobs can be completed in a timely manner. Third, supervision is also performed by employees, fourth, employee attendance does not guarantee the performance of employees in the work and the fifth, employees do not optimal conservation. It can be concluded that the three performance indicators according to Dessler, only three aspects that show the employee performance aspect of quality of work, quantity of work and supervision required. While the presence and conservation aspects do not yet optimal.